Intergenerational mobility in 19th-century Italy: A case study approach - Giuliana Freschi; Marco Martinez (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This paper aims at exploring the dynamics of intergenerational mobility of occupations in 19th-century Italy, by investigating the relationship between social mobility and industrialization at its very early stages. In this endeavor, we draw upon individual-level occupational data from marriage certificates collected from four different State archives for two benchmark years, 1815 and 1866. We follow a case-study approach, focusing on two medium-size cities and surrounding municipalities that would have played a role in the country's industrial development and two rural areas (Brescia, Salerno, the province of Udine, and Pisticci). Unlike most studies on intergenerational mobility, this paper provides estimates both on male and female mobility. Both men and women exhibited an increase in mobility throughout the 19th century, but the increase was more pronounced for women. This work makes a first attempt to investigate the drivers of mobility of occupations in pre-industrial Italy. In particular, we draw the attention on the association between literacy and social mobility. We explain the limited role of literacy in increasing social mobility rates by pointing out that, at the time, limited educational provision, particularly for girls, meant that being educated was a result of high social status rather than an active channel through which individuals could improve their occupational status through higher education
Keywords: J62; J16; N33; N93; 330; Social mobility; Literacy; Italy; Risorgimento; Gender